2009
DOI: 10.1080/10106040802460707
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between above-water surface and subsurface spectral reflectances collected over inland waters

Abstract: A comparison between above-water surface and subsurface spectral reflectances collected over inland waters Asif M. Bhatti Kochi University of Technology, Japan, asifmumtaz.bhatti@kochi-tech.ac.jp Donald RundquistUniversity of drundquist1@unl.edu John SchallesCreighton University, jfsaqua@creighton.edu Luis RamirezUniversity of Nebraska-Lincoln, luisermz@yahoo.com Seigo NasuKochi University of Technology, Japan Bhatti, Asif M.; Rundquist, Donald; Schalles, John; Ramirez, Luis; and Nasu, Seigo, "A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Chipman et al (2009) andOlmanson et al (2011) showed that all water bodies of 0.04 km 2 and larger are suitable for monitoring with this moderate resolution. However, their radiometric resolution and signal-to-noise ratio are not designed for a very low signal emanating from these waters (Arst 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Chipman et al (2009) andOlmanson et al (2011) showed that all water bodies of 0.04 km 2 and larger are suitable for monitoring with this moderate resolution. However, their radiometric resolution and signal-to-noise ratio are not designed for a very low signal emanating from these waters (Arst 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Underwater campaigns can vary in terms of the application of the data being investigated and the protocol necessary to capture the required data. Targets can include seagrass, macro-algae, corals and sponges and spectral measurements may be taken above surface or below surface: opinions differ on how inclusive a metadataset must be to document environmental and target properties [4,23]. The unique complexities of measuring targets and controlling influencing variables in a marine environment can be understood best by the scientists with in-field expertise.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, integration of field spectrometry data for interpretation of the remote sensing images is an essential component in the classification of small shallow water bodies. Future research in the field of spectrometry can be focused on subsurface measurement and influence of fluorescence on the water leaving signal [5,39]. Precise understanding of the light attenuation under shallow waters can lead to detail interpretation of upwelling radiance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it can be applied in the field by portable spectrometers [4]. Field spectroscopy has an important role in environmental science in which it allows to characterize the object being observed with in situ measurements [5]. With proper equipment and methodology, spectrometry can be conducted under a variety of conditions [6].…”
Section: Introductionmentioning
confidence: 99%